Health and Wellness Tourism Potential in Uzbekistan - Kudratov Mirjalol Khurshid ugli (Peerian Journals Publishing, 2025)
Health and wellness tourism is increasingly becoming an important sector in the developing Uzbekistan landscape because of its cultural heritage combined with historical importance. This article analyzes how Uzbekistan can utilize its native resources together with traditional customs and current infrastructure facilities to draw international wellness tourists worldwide. This research explores both prospects and obstacles as it analyzes Uzbekistan's standing in the worldwide wellness market evolution
Keywords: Uzbekistan; health tourism; wellness tourism; Silk Road